Pelaksanaan Pembelajaran Demokratis Oleh Guru PKn di SMPN 1 Candung Kabupaten Agam - Nila Sari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STKIP Ahlussunnah, 2020)
This research is behind the dilator because there are still civic education teachers whohave not carried out Civics learning democratically. This study aims to determine theimplementation of democratic learning in SMPN 1 Candung, and to describe theobstacles faced by Civics teachers in implementing democratic learning, and to analyzethe efforts that can be made in carrying out democratic learning at SMPN 1 Candung.This research is a qualitative research with descriptive method, the source of data istaken from the informants chosen by purposive sampling technique, data collection isdone through observation, interviews and documentation studies. Data analysistechniques using Miles and Hubersman data, namely data reduction, data presentation,drawing conclusions.Based on the research conducted, it was concluded that: 1) The implementation oflearning democratically by the Civics teacher at SMPN 1 Candung could be said to begood enough because the average implementation of learning was above 50%. 2) Theobstacle faced by Civics teachers in implementing democratic learning in SMPN 1Candung, Agam Regency is the lack of support from parents, the communityenvironment, limited funds, individual differences. 3) Efforts made in overcoming theproblems faced by Civics teachers in implementing democratic learning at SMPN 1Candung, Agam Regency are by raising awareness to parents to pay more attention totheir children and to be more involved in children's learning, increase communityparticipation in education, management classrooms to be more interesting.